Perspektiven auf Hochschullernwerkstätten Wechselspiele zwischen Individuum, Gemeinschaft, Ding und Raum - Tänzer, Sandra; Godau, Marc; Berger, Marcus; Mannhaupt, Gerd (Lernen und Studieren in Lernwerkstätten, 2019)
"Perspectives on University Learning Workshops" brings together conference papers from the 11th International Conference of University Learning Workshops in February 2018 in Erfurt. It invites you to immerse yourself in the broad discourse on conceptual considerations, research and practical experiences in and about university learning workshops. Emphasising the interplay of individual, community, thing and space, four thematic fields and interdependent relationships that are constitutive for university learning workshops will be addressed: What opportunities and challenges do learning workshops offer for individual development? How can cooperative and collaborative learning processes be promoted in communities? What is the significance of things, artefacts, media, technologies for learning and education in learning workshops? How are different discursive practices and learning processes realised in spaces and spatial constellations of learning workshops? Translated with www.DeepL.com/Translator (free version)